PENGARUH PEMBELAJARAN MATEMATIKA MODEL PROBLEM BASED LEARNING DAN DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII - Aurora Novianty; Aprilia Nurul Chasanah; Megita Dwi Pamungkas (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study was to compare the ability to critical thinking who were taught with PBL better than those taught with DL. The next objective’s the ability to critical thinking with PBL have achieved better completeness than with DL. This research uses research design that’s a quasi experiment form of nonequivalent post-test only control group design. Comparing the post-test results of two samples of 28 students from class VIII-B and 28 students from class VIII-C at SMPN 1 Secang who were selected randomly through a lottery. From Independent Sample t-Test test it produces a value of then is accepted, which means that the ability to critical thinking who were taught with PBL better than those taught with DL. Then the completeness proportion difference test’s carried out which produces a value of then is accepted which means the ability to critical thinking with PBL have achieved better classical completeness than with DL. From the results hypothesis testing, it can be concluded that the ability to critical thinking who were taught with PBL better than those taught with DL. Then the ability to critical thinking with PBL have achieved better completeness than with DL.